Labour market reforms in Korea to promote inclusive growth - Jones, Randall S.. (OECD Economics Department Working Papers, 2016)
Labour market reforms are essential to promote social cohesion by removing obstacles to employment, particularly for women, youth and older persons. In addition to reducing income inequality and poverty, such reforms would also sustain economic growth as Korea's working-age population begins to decline in 2017. Breaking down labour market duality is crucial to reduce the wide wage disparity. Better conditions for non-regular workers would in turn promote greater labour participation. Increasing the take-up of maternity and parental leave, expanding the availability of high-quality childcare, reducing working time, narrowing the large gender wage gap and eliminating discrimination would also increase opportunities for women. Boosting youth employment from its current low level requires addressing labour market mismatch by better aligning the skills learned in school with those demanded by employers. Reducing the emphasis on seniority in setting wages by moving to more flexible systems and expanding training to improve the skills of older persons would allow them to extend their careers, thereby reducing old-age poverty